Clinical and Neuroimaging Profile of Neonates With Moderate-to-Severe Encephalopathy Treated With Therapeutic Hypothermia. Issue 4 (December 2022) - Diggikar, Shivashankar; Venkatagiri, Praveen; Kulkarni, Srikanth; Sharma, Deepa; Chandra, Prathap
Objective: To demonstrate the clinical and neuroimaging profile of infants with moderate-to-severe encephalopathy after therapeutic hypothermia (TH) in the Indian setting. The secondary objective was to determine the logistics involved in performing neuroimaging in these infants. Design and Setting: A retrospective descriptive study in 2 tertiary centers. Methods: All infants who underwent cooling in both centers from January 2019 to December 2019 were included. Demographic data, details of cooling, clinical and neuroimaging profile (magnetic resonance imaging [MRI] and magnetic resonance spectroscopy [MRS]), and details of the logistics involved in performing the imaging (sedation, neonatal transport, personnel, distance traveled, and time taken) were collected and analyzed. Results: A total of 44 infants were enrolled of which 37 (84.0%) underwent both TH and neuroimaging (MRI and MRS). A total of 33 (75.0%) of infants were outborn, 20 (45.5%) of them had sentinel events before delivery and 17 (38.6%) were intubated at birth. Apgar score <5 min was seen in 8 (18.2%) and seizures in 23 (52.3%) of infants. A total of 37 (84.1%) survived until discharge and underwent neuroimaging. Neuroimaging was performed between 5 and 14 days after birth. The most common abnormal finding on MRI brain was the signal changes in watershed areas of brain 8 (18.2%) and on MRS was low N-acetyl aspartate and high lactate 13 (29.5%). Midazolam (68.2%) and Triclofos (15.2%) were the sedatives used during neuroimaging these infants. Conclusion: TH for infants with neonatal encephalopathy resulted in excellent survival outcomes in tertiary private sector hospitals.